2009
DOI: 10.1002/mma.1206
|View full text |Cite
|
Sign up to set email alerts
|

Zakharov–Shabat system and hyperbolic pseudoanalytic function theory

Abstract: In [1] a hyperbolic analogue of pseudoanalytic function theory was developed. In the present contribution we show that one of the central objects of the inverse problem method the Zakharov-Shabat system is closely related to a hyperbolic Vekua equation for which among other results a generating sequence and hence a complete system of formal powers can be constructed explicitly.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…where a and b are bicomplex functions of the variable z ∈ D. In [20], [23], [25] it was shown that many results from pseudoanalytic function theory [2] remain valid in the hyperbolic situation. We will not give here definitions and properties corresponding to the general Vekua equation (2.3) referring the reader to [23].…”
Section: Hyperbolic Vekua Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…where a and b are bicomplex functions of the variable z ∈ D. In [20], [23], [25] it was shown that many results from pseudoanalytic function theory [2] remain valid in the hyperbolic situation. We will not give here definitions and properties corresponding to the general Vekua equation (2.3) referring the reader to [23].…”
Section: Hyperbolic Vekua Equationmentioning
confidence: 99%
“…We use our recent result on the construction of the kernel of the transmutation operator corresponding to a Darboux associated Schrödinger operator [26] to find out that a bicomplex-valued function whose one complex component is the transmutation kernel K 1 (x, t) (for a Schrödinger operator d 2 dx 2 − q 1 (x), q 1 ∈ C[−b, b]) and the other complex component is K 2 (x, t) (for a Schrödinger operator d 2 dx 2 − q 2 (x), with q 2 obtained from q 1 by a Darboux transformation) is a solution of a certain hyperbolic Vekua equation of a special form (for the theory of elliptic Vekua equations see [47] as well as [2] and [23]). In spite of a recent progress reported in [20], [23], [25], [30] the theory of hyperbolic Vekua equations is considerably less developed than the theory of classical (elliptic) Vekua equations. For example, as was shown in [25] (see also [23]) the construction of so-called formal powers (solutions of the Vekua equation generalizing the usual complex powers (z − z 0 ) n ) can be performed using the definitions completely analogous to those introduced by L. Bers [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, Kravchenko et. al. show in [27] and [28] how hyperbolic numbers to analyze certain solutions to the Klein-Gordon equation. In 2014, Terlizzi, Konderak and Lacirasella provide many explicit formulae for functions over Lorentz numbers which they use to study manifolds modelled over Lorentz numbers [44].…”
Section: Historymentioning
confidence: 99%
“…In [10] and [4] "hyperbolic pseudoanalytic function theory" was studied where hyperbolic numbers D (also called duplex numbers) [16] defined by D := x + tj : j 2 = 1, x, t ∈ R ∼ = Cl R (0, 1) are considered instead of (elliptic) complex numbers. Here we show that the concept of the transplant operator can be introduced in this context as well and it allows one to solve hyperbolic main Vekua equations related to the Klein-Gordon equation.…”
Section: Hyperbolic Pseudoanalytic Function Theorymentioning
confidence: 99%